The Effect of Sales Promotion and Brand Awareness on Iconnet Purchase Decisions at PT. Icon+ in Makassar City - Ananda, Muhammad Fadly; Ruma, Zainal; Musa, Muh. Ichwan; Hasbiah, Siti; Wardhana Haeruddin, Muhammad Ilham (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of sales promotions and brand awareness on purchasing decisions for Iconnet at PT. Icon+ in Makassar City. The population in this study are Iconnet customers. Sampling in this study used the slovin formula so that 96 respondents were sampled. The type of research used is associative research. The data used is primary data obtained by distributing questionnaires to customers. The results of the study after being processed with SPSS 25 show that there is a partially significant effect between the independent variables on the dependent variable as evidenced by the t value of the sales promotion variable (X1) of 7.015 > t table of 1.661 with a sig. 0.000 < 0.05, and the calculated t value of the brand awareness variable (X2) is 2.873 > t table 1.661 with a significant value of 0.005 <0.05. Simultaneously there is a significant effect between the independent variable on the dependent variable as evidenced by the multiple linear regression equation Y = 4.565 + 0.302 X1 + 0.155 X2 +e and the significant effect of F count 41.345 > F table 3.094 with a significant level of 0.00 <0.05 The R Square value or the coefficient of determination of 0.471 indicates that 47.1% of the purchasing decision variable (Y) is influenced or can be explained by the independent variables of sales promotion and brand awareness, while the remaining 52.9% is explained by other variables not included in the this research. Based on this description.